Effect of Baking Temperature and Oil Content on Quality of Finger Millet Flour Cookies - Swami, Shrikant Baslingappa; Thakor, N. J.; Shinde, U. N. (Journal of Agricultural Engineering, 2014)
Finger millet flour along with other ingredients were used to develop cookies using varied oil content (30, 35 and 40%), baking temperature (180, 200 and 220°C) and time intervals keeping other ingredients (baking powder 0.7%, sugar 30%, vanilla flavour 2%) constant. The prepared cookies were tested for adjudging it’s textural (mainly hardness), colour and baking time. Sensory analysis of prepared cookies by nine-point hedonic scale indicated that the overall acceptability (colour, texture and flavour) of the cookies prepared with temperature at 200°C and 30 % oil content was more than the other samples.